Optimizing motor skills of first grade students through ninja warrior games - Pamungkas, Rifqi Nur Budi; Rindiana, Ririn Eka; Ma'arif, Rohmatulloh; Saputra, Roni; Zanuarta, Rozak; Ramadhani, Rizky; Hartati, Sasminta Christina Yuli; Yasik, Muhammad (Universitas Negeri Surabaya, 2025)
This study aims to improve the gross motor skills of first grade elementary school students through the application of the Ninja Warrior learning model in PJOK activities. This collaborative Classroom Action Research was conducted in two cycles. The subjects of the study were 24 students of class 1B SDN Jajartunggal 1/450 Surabaya in the 2024/2025 academic year. Data collection was carried out using a knowledge assessment in the form of a multiple-choice test to measure students' understanding of basic movement concepts, as well as a skills assessment through a performance observation sheet that assessed motor aspects, namely coordination, balance, and agility. Data analysis used descriptive Wilcoxon statistics. The results showed that the knowledge aspect increased significantly (Z = 3.230, p = 0.001 <0.05) from 65.3 in cycle I to 77.7 in cycle II, increasing by 19.0%. The skill aspect increased significantly (Z= 2.929, p= 0.003<0.05) from 66.0 in cycle I to 75.6 in cycle II, an increase of 14.7%. The conclusion of this study is that the Ninja Warrior model is effective as a physical activity-based PE learning strategy that is fun and structured in improving student learning outcomes, both in terms of knowledge and skills.